Short-term Revision Risk of Patellofemoral Arthroplasty Is High: An Analysis from Eight Large Arthroplasty Registries. Issue 6 (June 2020) - Lewis, Peter L.; Tudor, Francois; Lorimer, Michelle; McKie, John; Bohm, Eric; Robertsson, Otto; Makela, Keijo T.; Haapakoski, Jaason; Furnes, Ove; Bartz-Johannessen, Christoffer; Nelissen, Rob G. H. H.; Van Steenbergen, Liza N.; et al.
Abstract: Background: Patellofemoral arthroplasty (PFA) is one option for the treatment of isolated patellofemoral osteoarthritis, but there are limited data regarding the procedure and results. Because isolated patellofemoral arthritis is relatively uncommon, available case series generally are small, and even within national registries, sample sizes are limited. Combining data from multiple registries may aid in assessing worldwide PFA usage and survivorship. Questions/purposes: We combined and compared data from multiple large arthroplasty registries worldwide to ask: (1) What proportion of patients undergoing primary knee arthroplasty have PFA? (2) What are the patient and prosthesis characteristics associated with PFA in common practice, as reflected in registries? (3) What is the survivorship free from revision of PFA and what are the reasons for and types of revisions? Methods: Data were provided by eight registries that are members of the International Society of Arthroplasty Registries (ISAR) who agreed to share aggregate data: Australia, New Zealand, Canada, Sweden, Finland, Norway, the Netherlands, and the United States. De-identified data were obtained for PFA performed from either the beginning of year 2000, or the earliest recorded implantation date after that in each individual registry when PFA data collection commenced, up to December 31, 2016. This included patient demographics, implant use, all-cause revision rate (determined by cumulative percent revision [CPR]), and reasons for and type of revision. Results: During the data collection period, 6784 PFAs were performed in the eight countries. PFAs comprised less than 1% of primary knee replacements in all registries. Patient demographics were comparable in all countries. Patients were generally more likely to be women than men, and the mean age ranged from 50 years to 60 years. All registries showed a high rate of revision for PFA. The 5-year CPR for any reason ranged from 8.0% (95% CI 4.5 to 11.5) in Norway to 18.1% (95% CI 15.5 to 20.7) in the Netherlands. The most common reason for revision across all countries was disease progression (42%, 434 of 1034). Most PFAs (83%, 810 of 980) were revised to a TKA. Conclusions: The revision risk of PFA in all registries surveyed was more than three times higher than the reported revision risk of TKA at the same times. The survivorship of PFA is similar to that of the no-longer-used procedure of metal-on-metal conventional hip replacement. Although there may be potential functional benefits from PFA, these findings of consistent and alarmingly high rates of revision should create concern, particularly as this procedure is often used in younger patients. Level of Evidence: Level III, therapeutic study.